The image-informational model of the tragic character in Kazakh dramaturgy (based on the research of Rymgali Nurgali) - Turzhan О.; Abilkhan А.; Otarbayeva Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article presents a comprehensive analysis of the manifestation, function, and artistic nature of the concept of image—one of the key categories in contemporary humanities—within the art of tragic drama. The nature of tragedy is explored in connection with the national worldview, while the internal and external structure of the dramatic character and its semantic depth are examined as image-based technologies. These insights form the core of the article and pave the way for a reinterpretation of the tragic image in the aesthetic and communicative space of Kazakh drama. The study proposes new methodological approaches at the intersection of imagology and literary studies, and outlines a scientific model for understanding the structure of the tragic character through the lens of artistic imagery, personal-informational, and hermeneutic-communicative perspectives. The article aims to interpret the essence of national dramaturgy within the framework of modern scholarly concepts, drawing on the works of the dramatist and literary scholar, academician Rymgali Nurgali, to analyze the image-informational nature of tragic characters in dramatic works.